PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANIMAKER PADA MATA PELAJARAN AKIDAH AKHLAK MATERI AKHLAK TERPUJI KELAS VIII DI MTS BABUSSALAM HKSN MANGOLO - Muhammad Akbar; Nurhayati Nurhayati; Dzulfina Dzulfina (Jurnal Teknologi Pendidikan Madrasah, 2023)
This research aims to develop animaker-based learning media in supporting the teaching and learning process at MTs Babussalam HKSN Mangolo because basically learning media can attract the attention of students to be more focused on ongoing lessons. The formulation of the problem in this study is how is the design of the development of learning media based on the animaker application in the subjects of aqidah akhlak commendable morals material? and What is the level of effectiveness of learning media using the animaker application at MTs Babussalam HKSN Mangolo? There are two research objectives, namely to find out the design for the development of learning media based on animaker applications in aqidah moral subjects. To determine the level of effectiveness of learning media using the animaker application at MTs Babussalam HKSN Mangolo. This research method is research development or Research and Development using the Borg and Gall development model whose stages include potential and problems, data collection, product design, design validation, design revision, product testing; research subjects namely PAI teachers and class students. Research in the form of observation sheets, questionnaires, and interview guidelines for Akidah Akhlak teachers, and students. The results of the research show that this Animaker-based learning media includes potential and problems, data collection, product design, design validation, design revision, product trials. The Animaker learning media was declared effective because it met the criteria that became the reference, namely the response of students with a score of 89.99%. and the teacher's response to learning media with a value of 3.87.